Innovative Collaboration: The Ideal Path to Solving Global Environmental and Social Challenges - Harsh Moralikrushna Panchal (Marasofi International Media and Publishing (MIMP), 2025)
Global environmental and social issues such as climate change, pollution, and poverty remain persistent due to fragmented solutions and limited collaboration. This study aims to explore an ideal framework that integrates innovation with scientific and community-based collaboration to address these pressing challenges. A qualitative descriptive method was employed, utilizing literature review and case analysis of successful sustainability initiatives from different countries. The findings reveal that combining environmentally friendly technologies with active stakeholder collaboration—ranging from scientists to local communities—can produce scalable and sustainable solutions. Case studies highlight the success of renewable energy adoption, community-driven waste management, and reforestation efforts supported by digital platforms and policy integration. Discussions emphasize that while funding and political support are major barriers, leveraging global cooperation and inclusive education can enhance solution uptake. The study recommends fostering inclusive innovation ecosystems, strengthening international networks, and embedding sustainability principles in local development agendas. These efforts are essential to ensure that technological advancements are not only accessible but also culturally and socially embedded to achieve long-term global impact.